Cooling Circuit Model for Computer Simulator; Indian Journal of Science and Technology; Vol. 8, iss. 36 - Liventsova N. V. Nina Vladimirovna; Egorova O. V. Olga Viktorovna; Liventsov S. N. Sergey Nikolaevich; Larionova I. M. Inna Mikhaylovna; Blank M. O. Mariya Olegovna (2015, 2015)
Title screen